2003
DOI: 10.1021/je034016r
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Functions for Transfer of Anthracene from Water to (Water + Alcohol) Mixtures at 298.15 K

Abstract: The solubilities of anthracene in (1 -x)water + x ethanol and (1 -x)water + (x)tert-butyl alcohol mixtures (mole fractions of alcohol, x, from 0 to 0.8) have been determined at four different temperatures, 298.15 K, 303.15 K, 308.15 K, and 313.15 K, respectively. From the solubility data, the values of thermodynamic functions for the transfer of anthracene from water to (1 -x)water + x ethanol or to (1 -x)water + (x)tert-butyl alcohol mixtures were derived. The results are discussed on the basis of the sign of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The solubilities of a number of hydrophobic solid substances in water at room temperature have been investigated in recent years, and found to be as low as 10 –6 and even 10 –7 mole fractions. , However, numerous studies have also shown that the solubilities of hydrophobic compounds in liquid water increase dramatically above 100 °C. As a consequence of the dramatic increase in solvating power, subcritical water at relatively higher temperature has been shown to be a good alternative to organic solvents. Subcritical water processing has its advantages in that water is nontoxic, inexpensive, readily available, and easily disposed.…”
Section: Introductionmentioning
confidence: 99%
“…The solubilities of a number of hydrophobic solid substances in water at room temperature have been investigated in recent years, and found to be as low as 10 –6 and even 10 –7 mole fractions. , However, numerous studies have also shown that the solubilities of hydrophobic compounds in liquid water increase dramatically above 100 °C. As a consequence of the dramatic increase in solvating power, subcritical water at relatively higher temperature has been shown to be a good alternative to organic solvents. Subcritical water processing has its advantages in that water is nontoxic, inexpensive, readily available, and easily disposed.…”
Section: Introductionmentioning
confidence: 99%